RETRIEVING BROKEN INSTRUMENT IN HALF OF THE APIKAL ON CANINES TEETH WITH H-FILE BRAIDING TECHNIQUE - Styaningrum, Yunita; Andina, Yoanita Dwi; Kristanti, Yulita (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
ABSTRACTBackground: Broken instruments affect the outcome and prognosis. A broken instrument will prevent the procedure of cleaning and shaping, irrigation and obturation of the root canal on the obstructed root section causing failure in endodontic treatment. There are some treatments for broken instrument including retrieving a broken fragment file and bypassing it on the root canal. the aim of the case report aims to provide an alternative for retrieving broken instruments using the H-file braiding technique. Method: A 38-year-old female patient came to the Dental Conservation Clinic RSGM Prof. Soedomo FKG UGM. A patient got a history of initial root canal treatment in a clinic, which ended with a separated file on canine teeth left upper. No complain pain, from the investigation radiographic there is an instrument broken in half apical. The teeth 23 seen temporary restoration cavity class I is still in good. Retrieving broken instruments using the H-file braiding technique, preparation with step back techniques, obturation with warm vertical condensation technique and class I composite resin restorations with fiber-reinforced retention. Result: No complain pain after 2 weeks retrieving broken instrument.Conclusion: The technique of the H-file braiding technique is one technique to retrieve a broken instrument, this procedure is simple, cost-effective, harmless to the teeth and gives root canal sealing.